Oversubscription of Initial Public Offerings of SMEs in India : A Quantile Regression Analysis - Srivastava, Himadri; Solomon, Priya; Singh, Satyendra P. (Indian Journal of Finance, 2022)
The present study examined the problem of oversubscription and identified underlying variables/determinants. Further research has evaluated some variables primarily responsible for oversubscribing the initial public offerings (IPO) of small & medium enterprises (SMEs). The study analyzed the cross-sectional data of 431 SME initial public offerings issued from February 2012 to January 2020 and listed on NSE EMERGE and BSE SME platforms. The econometric techniques of OLS (ordinary least square) and quantile regression model were applied to test the study’s hypotheses. According to the findings, the independent variables such as issue size, issue price, pricing mechanism, and the listing delay had a negative effect. In contrast, the independent variables: firm size and under-pricing positively influenced the SME IPOs’ oversubscription in the sample period under study. The current study provided a few implications for the investors, advisors, and regulators operating in the stock market. For the investors, the study suggested certain essential factors to consider while buying SME IPOs. For the regulator, that is, SEBI, the study provided insights for framing guidelines and amendments to regulate the SME IPOs in the future. Further, the research also suggested the issuers (SMEs) should issue their IPOs when the buyers of the IPOs are driven to invest in the primary market with the objective of optimization of returns with potential growth in the future. This study included an extensive review of literature on the IPO market, with specific attention to the period after 2012, after the introduction of the SME trading platform in India.